THE IMPACT OF STRATEGIC VIGILANCE ON CRISIS MANAGEMENT: THE INTERACTIVE ROLE OF ORGANIZATIONAL LEARNING - AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF IRAQI - Hatem Kareem Mohammed Al-Bugharbee; Ahmed Ghorbel (Scholars Digest Publishing, 2024)
This current research aims to explore the impact of strategic vigilance in crisis management through the modifying role of organizational learning. In order to establish the intellectual and philosophical foundations, the researcher relied on the Azilal (2015:1) model to measure strategic vigilance, which consists of five dimensions (technological vigilance, competitive vigilance, community vigilance, environmental vigilance, marketing vigilance). And the (22: Huber, 1991) model to measure organizational learning, which includes four dimensions (knowledge acquisition, knowledge distribution, information interpretation, organizational memory). While crisis management was measured by the (Azoutar, 2021:23) model, which consists of four dimensions (early warning, control and preparedness, activity recovery, learning). The research relied on the questionnaire as the main tool for collecting data and information about the research community, which was represented by professors from the University of Wasit and the University of Karbala, while the researcher relied on (SPSS V.28 program) for statistical analysis and processing. In addition, the current research relied on the descriptive analytical approach. Based on the research problem and its hypotheses, the researcher reached a set of conclusions, the most prominent of which was that Wasit University and Karbala University have a special interest in creativity and sponsoring all creative steps taken by professors working in these two universities. The research resulted in a set of recommendations, the most important of which was supporting and encouraging all creative initiatives and steps taken by professors and employees at Wasit University and Karbala University in order to achieve the best quality of service and educational outcomes. Continuous openness to peer institutions and trying to benefit from the success stories achieved by these institutions and transfer them to Wasit University and Karbala University in order to reach advanced stages in higher education and scientific research.
Keywords: Strategic vigilance - organizational learning - crisis management - Wasit University - Karbala University.